2014
DOI: 10.1155/2014/708564
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Incontinence: Its Assessment and Relationship to Depression among Community-Dwelling Multiethnic Older Women

Abstract: Urinary Incontinence (UI) affects many older adults. Some of its deleterious consequences include stress, major depression, diminished quality of life, sexual dysfunction, and familial discord. Of the various mental health problems identified in the literature as being comorbid with UI, the most notable one continues to be depression. Despite a wealth of research contributions on this topic, the available literature is underrepresentative of ethnic minority older women. Culture has been shown to have a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…Hung et al [12] in a longitudinal study with a larger sample size using COX Regression analysis, showed that urinary incontinence can predict depression in postmenopausal women. Our results are hence consistent with the results of Bradley et al and Hung et al The reason for discrepancy between our results and those of Lagana et al [6] may be dueto the difference in the assessment tool; we used the BDI-II tool, while they used CES-D scale which reported no overall score of depression (only in dimensions).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Hung et al [12] in a longitudinal study with a larger sample size using COX Regression analysis, showed that urinary incontinence can predict depression in postmenopausal women. Our results are hence consistent with the results of Bradley et al and Hung et al The reason for discrepancy between our results and those of Lagana et al [6] may be dueto the difference in the assessment tool; we used the BDI-II tool, while they used CES-D scale which reported no overall score of depression (only in dimensions).…”
Section: Discussionsupporting
confidence: 89%
“…The results of this study showed that depression in postmenopausal women with urinary incontinence was higher in terms of severity and rate compared tocontrols. Bradley et al [19] and Lagana et al [6] conducted Figure 1. Box Plot of depression frequency in two study groups studies similar to our study using the comparative crosssectional design to examine the difference in depression level of women with and without urinary incontinence where the significant difference was reported only in Bradley et al's study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One study of UI and depression showed no association between the two in multiethnic older women. 17) However, another study indicated a threefold increase in depression in a group younger than 45 years compared to a group older than 45 years. 18) In our study, cerebrovascular disease was identified as a significant factor associated with UI.…”
Section: Discussionmentioning
confidence: 95%